Something Old, Something New: Ion Channel Blockers as Potential Anti-Tuberculosis Agents - Mitini-Nkhoma, Steven C.; Chimbayo, Elizabeth T.; Mzinza, David T.; Mhango, David V.; Chirambo, Aaron P.; Mandalasi, Christine; Lakudzala, Agness E.; Tembo, Dumizulu L.; Jambo, Kondwani C.; Mwandumba, Henry C. (Frontiers in Immunology, 2021)
Tuberculosis (TB) remains a challenging global health concern and claims more than a million lives every year. We lack an effective vaccine and understanding of what constitutes protective immunity against TB to inform rational vaccine design. Moreover, treatment of TB requires prolonged use of multi-drug regimens and is complicated by problems of compliance and drug resistance. While most Mycobacterium tuberculosis (Mtb) bacilli are quickly killed by the drugs, the prolonged course of treatment is required to clear persistent drug-tolerant subpopulations. Mtb’s differential sensitivity to drugs is, at least in part, determined by the interaction between the bacilli and different host macrophage populations. Therefore, to design better treatment regimens for TB, we need to understand and modulate the heterogeneity and divergent responses that Mtb bacilli exhibit within macrophages. However, developing drugs de-novo is a long and expensive process. An alternative approach to expedite the development of new TB treatments is to repurpose existing drugs that were developed for other therapeutic purposes if they also possess anti-tuberculosis activity. There is growing interest in the use of immune modulators to supplement current anti-TB drugs by enhancing the host’s antimycobacterial responses. Ion channel blocking agents are among the most promising of the host-directed therapeutics. Some ion channel blockers also interfere with the activity of mycobacterial efflux pumps. In this review, we discuss some of the ion channel blockers that have shown promise as potential anti-TB agents.